A brief, residential peer‐support retreat for trichotillomania: A mixed methods evaluation. (11th June 2019) - Slikboer, Reneta; Rehm, Imogen C.; Lam, Sandy; Maloney, Alycia; Nedeljkovic, Maja
Abstract: Evidence‐based psychological treatments for trichotillomania (TTM) can be effective; however, relapse is common and consumers have indicated poor satisfaction with treatment outcomes. The aim of this study was to identify participants' perspectives of critical factors associated with short‐ and long‐term recovery following their brief, intensive peer‐support retreat for TTM. A mixed methods longitudinal design was used to evaluate a 3‐day residential peer‐support retreat attended by eight women who self‐referred into the retreat. Semi‐structured interviews were conducted at post‐retreat ( n = 6) and 12‐month follow‐up ( n = 5). Self‐report measures of symptom severity, mood and quality of life were completed at baseline ( n = 7), post‐retreat ( n = 6), 6‐month follow‐up ( n = 5) and 12‐month follow‐up ( n = 5). An inductive thematic analysis was performed to identify themes within the interview transcripts. Quantitative outcome data was used to confirm, challenge, provide context for, and link qualitative findings within the broader literature. Quantitative outcome data demonstrated reduced TTM severity from baseline to post‐retreat. By 6‐month follow‐up, symptoms had relapsed to baseline levels. Participants' perspectives of factors associated with recovery immediately after the retreat included group‐based processes (e.g., sharing, normalisation, safety, and enhanced motivation/accountability) and individual processes (e.g., readiness for change, self‐regulation skills). The qualitative and quantitative data conveyed similar outcomes at both post‐retreat and 12‐month follow‐up. Brief, immersive peer‐support retreats for TTM may facilitate equivalent symptom reductions as longer, therapist‐delivered cognitive behavioural treatments for some individuals.